Theology of Education from Ibn Taymiyyah's Perspective and Its Relevance in Contemporary Times - Samsul Bahri; Halimatun Sakdiyah (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2025)
This study aims to describe the theology of Ibn Taimiya's thoughts and its relevance in the contemporary era. Therefore, this study uses library research with a descriptive analytical approach using comparative and historical methods. This study proves that Ibn Taimiyah's theology of education is placing Tauhid as the main foundation of the educational component, because from the basis of Tauhidlah, an educational concept can be built that will produce results and be beneficial for human life, even Ibn Taimiyah's educational concept is in line with the goals of National education which place faith and have faith in God Almighty as the first point.